Pendidikan Karakter dalam Kultur Globalisasi: Inspirasi dari Ki Hadjar Dewantara - Samho, Bartolomeus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2014)
Education is a wide terminology describing among others the transformative and liberatif activities of human being. One of the major aims of an education programme is to make a more balanced growth of a person’s characters, covering the intellectual, spiritual, social, emotional, and physical dimensions. In the light of Ki Hadjar Dewantara, the founder of Tamansiswa educational institution, one might say that education is an effort to advance the good characters (the inner strength and characters), the mind, and the body. For him, education is an effort to liberate the physical and spiritual aspects of a human being. Thus every activity in an education institution should be a process of humanisation that goes holistically, that is, physical, mental, spiritual, individual, sosial, cultural, dan natural growths. In line with this, a well educated person who has good characters may respect other people’s rights and could develop ecological concern. This article aims to explore how far education institutions can respond within the range of Ki Hadjar Dewantara’s concept of education to the globalization issues affecting our society today.